Antioxidant status of celery (Apium graveolens L.) - V. A. Kharchenko; A. I. Moldovan; N. A. Golubkina; A. A. Koshevarov; G. Caruso (Овощи России, 2020)
Relevance. Medicinal properties of celery (Apium graveolens L.) are connected to the most extent to high antioxidant status of plants.Material, methods and results. Comparative evaluation of polyphenols, ascorbic acid, flavonoids and photosynthetic pygments by leafy, stalk and root celery types, grown in similar conditions on experimental fields of Federal Scientific Center of Vegetable Production revealed several peculiarities, typical to each form. Antioxidant activity (AOA) of seeds, leaves and petioles composed a ratio: 2.7:1.74:1 for leafy form, 2.88:1.99:1 for stalk form, while root celery AOA of seeds, leaves, roots and petioles was characterized by a ratio 3.66:2.78:1.42:1. With practically no differences in leaves ascorbic acid content between different celery forms leaves:petioles ratio for ascorbic acid reached (5.31-5.57):1 for leafy and stalk forms whereas vitamin C distribution between leaves, roots and petioles of root celery was characterized by a ratio 8.1:1.1:1. Phenolics seeds:leaves:roots:petioles accumulation ratio for root celery was equal to 1.77: 1.77: 1.33:1, whereas leaves/petioles distribution of phenolicss in stalk andleafy forms reached 1.86:1 and 1.64:1 accordingly. Polyphenols content in seeds of leafy celery was 1.4-1.5 times lower than in leaves, contrary to stalk and root celery with equal concentrations of phenolics in seeds and leaves. Leaves/petioles ratio of flavonoids was the highest for Elixir (2.87) and Atlant culivars (2.41). Root and leafy celery Samuray cv demonstrated 1.54-1.71 appropriate values. The highest chlorophyll a and b content was typical for root celery. Celery antioxidant system was characterized by positive correlations between ascorbic acid, flavonoids, phenolics, zinc and total AOA and also between the AOA ratio seeds/petioles and leaves/petioles (r=+0.99; P<0.001) and a negative correlation between chlorophyll and phenolics and flavonoids accumulation levels. High nutritional significance of root celery leaves was estimated.